Carbon-doping-induced energy-band modification and vacancies in SnS2 nanosheets for room-temperature ppb-level NO2 detection. Issue 23 (7th October 2021) - Wu, Ruozhen; Hao, Juanyuan; Wang, Tingting; Zheng, Shengliang; Wang, You
Abstract : Carbon-doping mediated synergistic effect of energy-band modification and vacancy provides a new solution for developing high-performance LMDs-based gas sensors. Abstract : The two-dimensional layered metal dichalcogenides (LMDs) SnS2 is an interesting candidate for high-performance NO2 gas sensors. However, most SnS2 -based NO2 sensors are usually inert for detecting ppb-level NO2 at room temperature (RT) because of the intrinsic features of a large bandgap, poor conductivity, and lack of active sites. Herein, we successfully endowed SnS2 with ppb-level NO2 detection at RT by using a carbon (C)-doping strategy. Compared to the pristine SnS2 showing a negligible response toward NO2 at RT, the C-doped SnS2 exhibited an excellent response (481.3% for 1 ppm and 146.5% for 100 ppb) with full recovery. The sensitivity toward ppb-level NO2 was as high as 1200% ppm −1 . Moreover, the experimental and theoretical limit of detection (LOD) were down to 10 ppb and 0.3 ppb, respectively. Such impressive gas-sensing performance of C-doped SnS2 at RT was due to the doping-mediated synergistic effect of energy-band modification and the presence of an S vacancy. The results provide a real solution for developing high-performance LMDs-based gas sensors.